The Influence of Fashion Lifestyle, Sales Promotion, and Self Image to Impulse Buying Behaviour and Customer Satisfaction: (case study of student using the Shopee application at Narotama University Surabaya) - Dewi Mayasari; I Gede Arimbawa (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study is to analyze the influence of fashion lifestyle, sales promotion, and self image to impulse buying behaviour and customer satisfaction. Type of research is quantitative. The population of this study were 100 students who used the Shopee mobile application at Narotama Surabaya University. The analysis technique used is Partial Least Square. Data obtained from questionnaires and tasted with SmartPLS 3.0 application. The result of this study indicate that fashion lifestyle, sales promotion, and self image have a positive and significant influence on impulse buying behaviour and customer satisfaction. Impulse buying behaviour has a positive and significant effect on customer satisfaction.